“Evaluación de la solarización en la desinfestación de camas almacigueras para producir plantulas de tabaco ( nicotiana tabacum L) en San Martín - Apaza Mestancia, Eduardo Luis (2003)
Were investigated the time of solarization, in the disinfestations of beds almaciguents, toward produce plantules of tobacco in sector of Juan guerra - Region San Martin, during September to December of the 2001 . The design utilize was the DBCA with 12 treatments, 3 witness absolutes and another with bromide of methyl. Were solarize the substratum (60% soil clay, sandy and franc and 40% humus the worm ), during 1 O, 20, 30, and 40 days, being used plastics transparent of 80 um of thickness; being compared with witness without solarize and another with bromide of methyl to dose of O, 15 lb/m2 . During the time that lasted the solarization they registered the temperatures of the soil and of the atmosphere. Were realization evaluations to the substratum with emphasis in nematodes and mushrooms, and to level of almacigue presence of overgrowths, weight humid and weight dry of the seedling. The results were expressed in percentages in the different evaluations. To from of 20, 30 and 40 days of solarization were achieved reductions considerate of nematodes, (Pratylenchus sp., Paratylenchus sp., Tylenchus sp.) of 99% to 100% in the different treatments, and mushrooms pathogens, (Phytophthora, sp Fusarium sp.) of 60% to 98%, and overgrowths monocotyledonous and dicotyledonous, (Amaranthus sp., Euphorbia sp., Cyperus sp, Rotboella sp) of 55% to 97%, the weight humid and dry off they obtained increments in weight to more day of solarization respectively. The treatment with bromide of methyl their control was of 90% to 100%. The antecedents generals indicate that the method solarization allows lower the occurrence of microorganism's pathogens and overgrowths. The results obtained demonstrate that with the solarization were can gain a control adequate the diverse plagues in the disinfestations of beds of tobacco. In connection with the analysis economic, it indicates that the treatment with 40 days was who obtained an major B/C of 1,21 in connection with the other treatments evaluated.